2017
DOI: 10.1371/journal.pone.0182117
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor-associated autoantibodies as diagnostic biomarkers for lung cancer: A systematic review and meta-analysis

Abstract: ObjectiveWe performed a comprehensive review and meta-analysis to evaluate the diagnostic values of serum single and multiplex tumor-associated autoantibodies (TAAbs) in patients with lung cancer (LC).MethodsWe searched the MEDLINE and EMBASE databases for relevant studies investigating serum TAAbs for the diagnosis of LC. The primary outcomes included sensitivity, specificity and accuracy of the test.ResultsThe systematic review and meta-analysis included 31 articles with single autoantibody and 39 with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 88 publications
2
46
0
Order By: Relevance
“…One recent review [109] indicated different single or combinations of multiple TAAbs have different diagnostic abilities for detecting patients at all stages of lung cancer, while the review did not report sensitivity, specificity and AUC for each TAAb. In our systematic review, each TAAb was analyzed using bivariate mixedeffect models, and larger numbers of references were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent review [109] indicated different single or combinations of multiple TAAbs have different diagnostic abilities for detecting patients at all stages of lung cancer, while the review did not report sensitivity, specificity and AUC for each TAAb. In our systematic review, each TAAb was analyzed using bivariate mixedeffect models, and larger numbers of references were included.…”
Section: Discussionmentioning
confidence: 99%
“…Other TAAbs were excluded from the review because relevant data were available from fewer than 3 articles . Five of the included studies examined only small-cell lung cancer (SCLC) [45,50,52,58,67], and eight included only non-small cell lung cancer (NSCLC) [28,47,54,55,57,59,64,109]. A total of 50 articles were based on serum specimens, while the remaining 3 were based on plasma samples.…”
Section: Basic Information About the Included Studiesmentioning
confidence: 99%
“…The higher sensitivity and specificity of P53 AAb for high-grade serous tumors is likely related to the uniform occurrence of P53 mutations, with dysregulated P53 protein levels, in high-grade serous tumors. Like the P53 AAbs, elevated titers of AAbs to the cancer-testis antigens CTAG1A (NY-ESO-1) and CTAG2 (ESO2) have been observed in relation to a wide variety of cancer types 6814, 15 , including ovarian cancer 20913 , and are likely related to the generally less differentiated nature of cancer cells, with aberrant expression of proteins that normally are expressed only in embryonic tissue types. AAbs to NUDT11 were first discovered as ovarian autoantigens through our own immuno-proteomic screening of ovarian cancer patients and controls 18 .…”
Section: Discussionmentioning
confidence: 99%
“…of AAbs to the cancer-testis antigens CTAG1A (NY-ESO-1) and CTAG2 (ESO2) have been observed in relation to a wide variety of cancer types, [6][7][8]14,15 including ovarian cancer, 9,13,20 and are likely related to the generally less differentiated nature of cancer cells, with aberrant expression of proteins that normally are expressed only in embryonic tissue types. AAbs to NUDT11 were first discovered as ovarian autoantigens through our own immuno-proteomic screening of ovarian cancer patients and controls.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation